The Consequence of Price and Location Factors in Purchasing Decisions at Kokoh City Madura: A Qualitative Analysis - Sutrisno, Ricy (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This research investigates the important factors that influence house purchasing decisions, specifically focusing on price and location, within the Kokoh City Madura housing complex. Using a qualitative case study approach, interviews with homeowners were conducted to analyze these variables. These findings confirm that price and location are the dominant determinants in the home purchasing decision making process. The study concluded that housing developers should prioritize these factors to improve sales and consumer decisions. Currently capable of accommodating 600 families, Kokoh City housing has attracted the interest of residents, especially from the city of Surabaya, because of its affordable price and strategic location, only 30 minutes from the city center. Accessibility and minimal traffic jams contribute to the housing’s attractiveness. The observed spike in purchasing decisions underscores the impact of price and location, validated through previous statements and research. Practically, this research provides information to property buyers regarding the important role of price and location in the decision-making process, emphasizing the importance of informed choices in residential property investment.